2015
DOI: 10.1002/aur.1569
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia in children with and without autism spectrum disorders

Abstract: Alexithymia refers to pronounced difficulty in identifying and describing one's own emotions and is associated with an externally oriented focus of thinking. Alexithymia is known to be much more common in adults with autism spectrum disorders (ASD) compared with the typically developing (TD) adult population. However, we know very little about alexithymia in young children with ASD and advancing our understanding of this topic may be of critical clinical and translational importance. Here, we present the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
90
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(106 citation statements)
references
References 24 publications
14
90
2
Order By: Relevance
“…Importantly, the two groups were matched on measures of verbal (and nonverbal) IQ, and verbal IQ was not significantly associated with alexithymia, indicating the higher CAM scores in the ASD group were not explained by lower verbal ability. This finding replicates the large group differences in CAM scores between children with and without ASD reported by Griffin et al [47] and complements studies showing higher rates of alexithymia in adults with ASD [8, 67]. …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Importantly, the two groups were matched on measures of verbal (and nonverbal) IQ, and verbal IQ was not significantly associated with alexithymia, indicating the higher CAM scores in the ASD group were not explained by lower verbal ability. This finding replicates the large group differences in CAM scores between children with and without ASD reported by Griffin et al [47] and complements studies showing higher rates of alexithymia in adults with ASD [8, 67]. …”
Section: Discussionsupporting
confidence: 90%
“…In addition to using the CAM, Griffin et al [47] assessed alexithymia using the Children’s Alexithymia Questionnaire-Self Report (CAQ-SR; [68]). While both measures were sensitive enough to demonstrate higher levels of alexithymia in the ASD participants, correlational analyses revealed no relationship between the two measures indicating that children and their parents may be using different sources of information or that the content of the respective measures is highly dissimilar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has an impact at both intrapersonal and interpersonal levels and has been linked to socio-affective deficits such as a lack of empathy (Guttman and Laporte 2002). The few studies that have examined alexithymia in children with ASD have found that, similarly to adults (Berthoz and Hill 2005), alexithymia is more prevalent among children with ASD than among TD children (Griffin et al 2015;Rieffe et al 2007). In one study it was found that the facial expressions of individuals with higher levels of alexithymia appeared to be odder than of those with lower levels (Brewer et al 2016).…”
Section: Emotional Response Incoherence In Asd and The Role Of Alexitmentioning
confidence: 99%
“…But this simplistic picture is further complicated in light of the new insights provided by the alexithymia hypothesis 3 which postulates that only the deficits observed in the sociocognitive domain are unique to the autism phenotype, while the deficits associated with socioaffective domain are due to the co-occurring alexithymic phenotype and is not a feature of autism per se 27 . Although the preponderance rate of clinical levels of alexithymia in healthy population is at 10%, it is unusually prevalent (40-65%) in adults and children with ASD [28][29][30][31][32] . Therefore, it is important to account for its effects in emotional processing deficits observed in ASD, especially because trait alexithymia itself has been associated with impaired emotional processing (e.g., empathy [33][34][35] , emotion regulation 36 , emotional interoception 37 , etc.).…”
mentioning
confidence: 99%